(untitled) (Szociológiai Szemle, 2024)
Using empirical data and other sources the study presents those ’institutions’ (real estate brokerage firms and classified advertisements) which help make deals between players in the private rental market. The common experience and our data justify that the actors of the demand and supply sides often look for and find landlords or tenants using their personal networks because the above mentioned ’institutions’ of the market work deficiently and expensively. The rent level is lower and the direct or indirect connection between partners gives guarantee for both sides in those cases where the personnel network plays a decisive role in creating the business. This first view of the role of the ’network of contacts’ helps explore the reasons which increase transaction cost in the private rental market and can cause increased social cost in the Hungarian housing system.